2002
DOI: 10.1097/00126334-200211010-00008
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Dysfunction in HIV-Infected Patients Treated With Highly Active Antiretroviral Therapy

Abstract: Sexual disturbances develop in some patients treated with highly active antiretroviral therapy (HAART). To evaluate sexual dysfunction and the influence that different antiretrovirals could have on those parameters, we conducted a prospective study in patients with stable clinical condition attending an HIV outpatient clinic. A total of 351 evaluations were performed in 189 HIV-infected men, who were interviewed about symptoms of sexual dysfunction. Sexual hormones as well as other clinical and laboratory para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
65
2
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(81 citation statements)
references
References 18 publications
7
65
2
1
Order By: Relevance
“…While several studies have demonstrated an association with PIs (1,2,3,5) it is interesting that neither of the two groups that utilised the IIEF found a link with a particular class of medications (4,6).…”
Section: Erectile Dysfunctionmentioning
confidence: 99%
See 1 more Smart Citation
“…While several studies have demonstrated an association with PIs (1,2,3,5) it is interesting that neither of the two groups that utilised the IIEF found a link with a particular class of medications (4,6).…”
Section: Erectile Dysfunctionmentioning
confidence: 99%
“…Deleted: There have been numerous reports of sexual dysfunction in HIV positive men with prevalence rates of up to 70% being described (1)(2)(3)(4)(5)(6) The primary objectives of this study therefore are to establish the prevalence of erectile dysfunction (EDF) and low sexual desire (LSD) in both ARV naïve and experienced HIV positive men attending HIV outpatient centres across Europe and to define the variables associated with sexual dysfunction. Due to the large number of variables that are potentially contributors to dysfunction a large amount of data relating to these variables was collected.…”
Section: Deleted: Sep_06mentioning
confidence: 99%
“…Currently, little is known about whether the impact of being HIV-positive on sexuality has changed with the availability of HAART and the subsequent reconceptualization of HIV as a chronic disease rather than an acute life-threatening illness. HAART use has been linked to higher prevalence of sexual dysfunction among HIVinfected men (Collazos, Martinez, Mayo, & Ibarra, 2002;Colson et al, 2002;Lamba et al, 2004;Schrooten et al, 2001). Although the relationship between HAART and sexual functioning remains far less examined among HIV-positive women, the little research that has been done has found few differences.…”
Section: Introductionmentioning
confidence: 99%
“…Another study also reported that there was sexual dysfunction experienced by 51% of PLWHA seeking for the treatment by ARV. About 46% of them experienced erectile dysfunction, 39% experienced ejaculation disorder, and 27% had orgasm disorder (Collazos, 2007).…”
mentioning
confidence: 99%